2021
DOI: 10.1002/chem.202103078
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism‐Based Approach to Reagent Selection for Oxidative Carbon−Hydrogen Bond Cleavage Reactions

Abstract: Numerous hydride-abstracting agents generate the same cationic intermediate, but substrate features such as intermediate cation stability, oxidation potential, and steric environment can influence reaction rates in an oxidantdependent manner. This manuscript provides experimental data to illustrate the role that structural features play in the kinetics of hydride abstraction reactions with commonly used quinone-, oxoammonium ion-, and carbocation-based oxidants. Computational studies of the transition state st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The activation free energies in this work were higher than expected, most likely as a result of the calculated products having the ( Z )-geometry for the oxocarbenium ion rather than the more favorable ( E )-geometry. A subsequent investigation by Miller, Zhou, and co-workers showed 42 that transition state free energies more closely match experimental results when the reaction pathway provides the ( E )-oxocarbenium ion, and that the rates of these reactions are generally much greater than those of corresponding oxidations by DDQ when both reactions are conducted in acetonitrile. This work also showed that, in contrast to DDQ reactions, oxidations by oxoammonium ions are not sensitive to substrate oxidation potential and cation stability is the defining factor in hydride abstraction rates.…”
Section: Oxoammonium Ionsmentioning
confidence: 84%
See 3 more Smart Citations
“…The activation free energies in this work were higher than expected, most likely as a result of the calculated products having the ( Z )-geometry for the oxocarbenium ion rather than the more favorable ( E )-geometry. A subsequent investigation by Miller, Zhou, and co-workers showed 42 that transition state free energies more closely match experimental results when the reaction pathway provides the ( E )-oxocarbenium ion, and that the rates of these reactions are generally much greater than those of corresponding oxidations by DDQ when both reactions are conducted in acetonitrile. This work also showed that, in contrast to DDQ reactions, oxidations by oxoammonium ions are not sensitive to substrate oxidation potential and cation stability is the defining factor in hydride abstraction rates.…”
Section: Oxoammonium Ionsmentioning
confidence: 84%
“…41 The impact of steric effects on oxidation rate was established in an experimental and computational study by Miller, Zhou, and co-workers. 42…”
Section: Quinone Oxidantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This selectivity is now understood to originate from the unique property that the oxidations occur via a hydride transfer from the substrate to the oxoammonium salt under acidic or neutral conditions (Scheme 2). 11,17–19…”
Section: Recent Developments In the Mechanistic Understanding Of Oxoa...mentioning
confidence: 99%